2002
DOI: 10.1101/gad.1018902
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of RNA polymerase III to its target promoters

Abstract: A key step in retrieving the information stored in the complex genomes of eukaryotes involves the identification of transcription units and, more specifically, the recognition of promoter sequences by RNA polymerase. In eukaryotes, the task of recognizing nuclear gene promoters and then transcribing the genes is divided among three highly related enzymes, RNA polymerases I, II, and III. Each of these RNA polymerases is dedicated to the transcription of specific sets of genes, and each depends on accessory fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
610
1
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 540 publications
(625 citation statements)
references
References 231 publications
(330 reference statements)
11
610
1
3
Order By: Relevance
“…These were situated upstream of a likely TSS location as indicated by RNA Pol. III PSE, a strong determinant for the recruitment of RNA polymerase III (Schramm & Hernandez, 2002). These potential transcription factor‐binding sites strongly suggested that STAT activation could contribute to the upregulated expression of miR‐7.…”
Section: Resultsmentioning
confidence: 99%
“…These were situated upstream of a likely TSS location as indicated by RNA Pol. III PSE, a strong determinant for the recruitment of RNA polymerase III (Schramm & Hernandez, 2002). These potential transcription factor‐binding sites strongly suggested that STAT activation could contribute to the upregulated expression of miR‐7.…”
Section: Resultsmentioning
confidence: 99%
“…These studies, combined with sequence analysis, have shown that 9 out of 13 conserved TAF subunits have histone fold domains (HFDs) 61 . TAFs form at least 5 histone-like pairs essential for the function of TFIID (6)(7)(8)(9)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Mapping the location of the HFD TAFs to the TFIID structure using electron microscopy has given unexpected results 62 , the most surprising of which is that the TAFs shared between TFIID and SAGA are not found in a substructure of TFIID but are distributed among the three lobes.…”
Section: Tafs Are Shared Subunits Of Two Large Complexesmentioning
confidence: 99%
“…However, their delivery strategies did not target a specific cell population due to the ubiquitous existence of Pol-III activity in all cell types. Because the readthrough side-effect of Pol-III occurs on a short transcription template if without proper termination, large RNA products longer than desired 18-25 base-pairs (bp) can be synthesized and then cause unexpected interferon cytotoxicity [40,41]. Such a problem can also result from the competitive conflict between the Pol-III promoter and another vector promoter (i.e.…”
Section: Advantages Of Mirna-mediated Rnai Mechanismmentioning
confidence: 99%